CASE STUDY: APPLICATION OF ACTIVE RANGE OF MOTION (ROM) EXERCISES TO IMPROVE MUSCLE STRENGTH IN RHEUMATOID ARTHRITIS PATIENT - Nurmaya Fauztina Fauzani; Made Sumarwati; Hikmi Muharromah Pratiwi (International Journal of Biomedical Nursing Review, 2025)
Introduction: Rheumatoid arthritis is a disease that attacks the joints which can cause a decrease in muscle strength. To avoid a decrease in muscle strength, non-pharmacological treatment can be done by doing Range of Motion (ROM) exercises. Purpose: This case study aims to determine the increase in muscle strength in patients with rheumatoid arthritis after active ROM exercises. Methods: The method used is a case study using descriptive research. The subject of the study is one patient with rheumatoid arthritis. The focus of this study is on the application of evidence-based nursing in the form of active ROM exercises for 3 times in 3 consecutive days with a movement frequency of 10 times to patient with rheumatoid arthritis. Muscle strength assessment is carried out using Manual Muscle Testing (MMT) to see the results of the pre-test and post-test of the patient's muscle strength. Discussion: The results obtained after the patient underwent active ROM exercises were increased muscle strength. Active ROM exercises was able to increase muscle strength from 4/4/3/3 to 5/5/4/4. This shows that ROM exercises can be used as a therapy to increase muscle strength in patients with rheumatoid arthritis. Conclusion: Providing active ROM exercises can increase muscle strength in patients with rheumatoid arthritis.